EFFECT OF INTEREST IN LEARNING AND MEDIA LEARNING ON LEARNING OUTCOMES OF INFORMATION TECHNOLOGY LESSON - Noviyanti, Yohana Budi (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2015)
The purpose of this research is to analyze the effect of partial and simultaneous interest in learning and media learning on learning outcomes of Information Technology X grade Office Administration Vocational High School 3 Surakarta. The method used in this research is descriptive quantitative. Sampling technique in this research is sampling saturated. The samples in this research were all X grade of Office Administration. The results of the data analysis and discussion stating that (1) there is positive and significant correlation between interest in learning to learning outcomes of Information Technology subjects. (2) the influence of media learning to learning outcomes of study subjects Information Technology. (3) there is positive and significant correlation between learning and learning media together to learning outcomes of Information Technology subjects. (4) the results of the calculation value data R Square of 0.235 indicates that 23.5 percent of the variables learning outcomes can be explained by the variable interest in learning and instructional media. The remaining 76.5 percent is explained by other variables beyond the variables used in this study. The relative contribution of the media interest in learning and learning on learning outcomes of information technology subjects in the amount of 44.95 percent and 55.05 percent. Keywords: interest in learning, media learning, learning outcomes.